Climate conflict in Clive and Dirk Cussler’s action thriller Arctic Drift - Ghasemi, Mehdi; Korkka, Janne; Valovirta, Elina (Informa UK Limited, 2025)
This paper offers a close reading of Clive and Dirk Cussler’s Arctic Drift (2008) with a focus on the novel’s engagement with human exploration and exploitation of the Arctic and its resources. To study climate and conflict in the novel, we draw upon the Arctic’s potential as a geopolitical arena where territorial claims, resource competition, and environmental challenges give rise to both confrontation and collaboration. We also show how the novel rehistoricises the final Franklin expedition to the Northwest Passage (1845 onwards) and examine the techniques that the authors employ to raise scepticism towards a number of historical and scientific metanarratives with their revisionist narrative. Building on this, the paper investigates how the novel critiques the persistence of colonial ideologies in Arctic discourse, depicting corporate and governmental interests as extensions of historical imperialism. Further, the paper demonstrates how the ecological narrative of the novel draws upon the constantly shifting and mutating ecosystems of the Canadian Arctic and negotiates the significance of sustainability in the endangered circumpolar North.